If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -2a = 0 Reorder the terms: -2a + -4x = 0 Solving -2a + -4x = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '4x' to each side of the equation. -2a + -4x + 4x = 0 + 4x Combine like terms: -4x + 4x = 0 -2a + 0 = 0 + 4x -2a = 0 + 4x Remove the zero: -2a = 4x Divide each side by '-2'. a = -2x Simplifying a = -2x
| (.75)x+(.625)-(.5)x=(1.5)x-(2.5) | | (5x+2)/(4x+7)=x | | (5x+2)/(4x+7) | | (3/4)x-6=x+5 | | 1-1/x-8 | | 1+1/x-8 | | -8x+10=5x+9 | | 2(x-5)(x-5)=0 | | xx-2x+1=0 | | (3d-7)+8=0 | | 7/4u=1/2-1/6v | | y+-4y=118 | | 5x-(17*13)/122=2 | | (6y+5)+(2y-6)=118 | | (6y+5)+(2y-6)= | | 1x+20+2x=-10-2x-15 | | 16x+8x=192 | | 9+3x=14+2x | | (1800+x)/(25+y)=80 | | (3y+5)+(y-6)=118 | | 10cos(10x)=0 | | (-(-3x-5y)/4x)-((4x+9y)/4x)=0 | | 8x+4x=192 | | (7x+1)-(x-5)=6 | | 7x+1-5x=6 | | 2.5=(540-x)/x | | x+raiz(x-1)=13 | | 2.5X=540-x | | 2.5X=240-X | | y=14x^2-56 | | 2/3x+12=8 | | x-5/2x+15=0 |